Case of a lung collision tumor consisting of squamous cell carcinoma of the lung and diffuse large B‐cell lymphoma. Issue 7 (15th July 2022) - Sasaki, Masato; Sakon, Kayo; Tanaka, Kaede; Okada, Akitoshi; Ikeda, Takeshi; Koshiji, Takaaki
Abstract: Among the reports of malignant collision tumors, collision tumors consisting of lung cancer and malignant lymphoma are extremely rare. We report case of a lung collision tumor consisting of squamous cell carcinoma of the lung and diffuse large B‐cell lymphoma. Abstract : We report rare case of a lung collision tumor consisting of carcinoma of the lung and malignant lymphoma. Physicians must consider which treatment should be prioritized according to the degree of progression of coexisting solid tumors